CLEAR PROGRESS IN E-GOVERNMENT QUALITY ACTIVITIES AND DETERMINING THE AREAS OF APPLICATION OF E-GOVERNMENT FOR THE BENEFIT OF DEVELOPING COUNTRIES DURING A COVID PANDEMIC - Ban Qasim Al nidawy; Balqees Naji Ajel (Galaxy International Interdisciplinary Research Journal, 2023)
The objective of this study is to provide a clear understanding of the concept of e-government by examining the benefits it offers to both societies and individuals, as well as the challenges that hinder the implementation of electronic governance, particularly in developing countries. Additionally, this study seeks to explore the impact of the COVID-19 pandemic on the adoption and application of e-government.